Assessing telehealth interventions for physical activity and sedentary behavior self‐management in adults with type 2 diabetes mellitus: An integrative review. Issue 1 (22nd October 2020) - Howland, Chelsea; Wakefield, Bonnie
Abstract: Type 2 diabetes is a chronic disease, requiring lifestyle management to prevent chronic complications. Increasing physical activity and reducing sedentary behavior are integral to maintaining glycemic control. The purpose of this study was to (1) appraise and synthesize the literature about physical activity and sedentary behavior intervention delivery via telehealth strategies in adults with type 2 diabetes mellitus and (2) to evaluate what is known about the effectiveness of such interventions on physical activity, sedentary behavior, and glycemic control. An integrative literature review was carried out, including the electronic databases PubMed, CINAHL, and PsychInfo, searching for articles published within the past 10 years, meeting specified inclusion and exclusion criteria, following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement guidelines. Seventeen studies were included. Significant improvements in physical activity and sedentary behavior were identified in web and mobile phone‐based interventions. Modest improvements in glycemic control were reported. Theoretical framework use and integration was limited, and intervention length and follow‐up varied greatly in the studies reviewed. Outcomes were measured using both self‐report and objective measures, but objective measures were used less frequently. Further, few studies have been conducted in the United States or in rural populations. Web and mobile phone‐based telehealth interventions to increase physical activity, reduce sedentary behaviors, and improve glycemic control have been supported by the literature. A need exists for future studies that are theory‐driven, include dose‐specific measures, self‐report and objective measures, and long‐term follow‐up. Examining intervention effects in rural populations is needed.